Treatment of subarachnoid-parenchymal hemorrhage, caused by rupture of the middle cerebral artery aneurysm - Tsimeyko, Orest; Novikov, Ruslan (Ukrainian Neurosurgical Journal, 2014)
Clinical observation of treatment of rupture of the right middle cerebral artery aneurysm with subarachnoid-parenchymal hemorrhage (V graduation on Hunt-Hess scale) is given. Taking into account the patient’s condition, urgent surgical treatment was held, aimed at removing the source of bleeding and increasing the intracranial volume (advanced craniotomia). This contributed to significant improvement: consciousness recovering, spontaneous breathing, swallowing, minimal movements in patient’s left upper extremity.